ANALISIS KOMPARASI HARGA, KUALITAS PELAYAN DAN CITRA MEREK TERHADAP KEPUASAN PASIEN RAWAT JALAN: Studi kasus Rumah Sakit Islam Ahmad Yani Dan Rumah Sakit Bhayangkara Surabaya - Muslimah Anissa (KELOMPOK KOMUNITAS LABORATORIUM PENELITIAN, 2022)
This study aims to determine wheter there are differences in the effect of price, service quality and brand image on outpatient satisfaction at Ahmad Yani Islamic Hospital and Bhayangkara Hospital Surabaya. For the sampling technique using purposive sampling , the sample size used was 100 respondents, divided into two, 50 respondents from Ahmad Yani Islamic Hospital and 50 respondents form Bhayangkara Hospital Surabaya. Collecting data using an online questionnaire or google form, then the data is processed using SPSS software using the Validity Test and the Independet Sample T test. The result of the analysis using the Independent Sample T tes are : 1. There is no significant different between the Price variabels at Ahmad Yani Islamic Hospital Surabaya and Bhayangkara Hospital Surabaya with a value of (sig-t) 0,656 > 0.05 meaning the hypothesis rejected. 2. There is a siginificant difference between the Service Quality Variabels at Ahmad Yani Islamic Hospitalc Surabaya and Bhayangkara Hospital Surabaya with a value of (sig-t) 0.026 < 0.05 meaning that the hypothesis is accepted. 3. There is no significant difference from the Brand Image Variable at Ahmad Yani Islamic Hospital Surabaya and Bhayangkara Hospital Surabaya with a value of (sig-t) 0.970 > 0.05 meaning that the hypothesis is rejected. 4. There is a significant difference from the Patient Satisfaction variable at Ahmad Yani Islamic Hospital Surabaya and Bhayangkara Surabaya with a value (sig-t) of 0.001 < 0.05 meaning that the hypothesis is accepted.